1999
DOI: 10.1111/j.1572-0241.1999.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, Nitric Oxide, and the Clinical and Hemodynamic Alterations of Patients With Liver Cirrhosis

Abstract: Although the activity of the nitric oxide pathway is increased in patients with cirrhosis and might contribute to the hemodynamic alteration, other factors are involved. Interleukin-6, possibly through nitric oxide-independent mechanisms, also might play a role in the vasodilatation of cirrhosis and the pathogenesis of hepatic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(30 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…Plasma concentrations of inflammatory cytokines are increased in these patients, even in the absence of active infection (19,50,55), and this activation of inflammatory mediators might explain the decrease in HRV observed in these patients.…”
mentioning
confidence: 99%
“…Plasma concentrations of inflammatory cytokines are increased in these patients, even in the absence of active infection (19,50,55), and this activation of inflammatory mediators might explain the decrease in HRV observed in these patients.…”
mentioning
confidence: 99%
“…For example, NO is a potent inducer of increased membrane permeability in the vascular endothelium and intestinal mucosa, possibly contributing to the accumulation of ascites and to bacterial translocation [31] . In the current study, although TNF-α was thought to induce NO synthesis (NOS) through the inducible NOS and endothelial NOS [32,33] , there was no significant correlation between TNF-α level and NO level in LC. This is the same to some studies, where such a relation could not be observed [34,35] .…”
Section: Cirrhotics Without Ascites (N = 27)mentioning
confidence: 83%
“…Animal studies suggesting that inflammationassociated alterations may contribute to cognitive impairment in hepatic encephalopathy [32]. Higher levels of TNFα and IL-6 are detectable in the serum of patients with fulminant hepatitis and cirrhosis [33,34] and inflammatory cytokines in patients with infections and liver disease could influence brain function at different levels including the cerebral endothelial cell and Astrocytes [35]. Our finding revealed a relation between Ozone concentration and hepatic encephalopathy severity which further support the potential role of inflammatory cytokines on brain function among cirrhotics although our study has some limitation.…”
Section: Discussionmentioning
confidence: 99%